The Effect of Cooperative Learning on Improving High School Students' Chemistry Learning Outcomes in Indonesia: Systematic Literature Review - Friska Nathalia Br S. Brahmana; Komang Treasia Maharani; I Wayan Redhana (Jurnal Pendidikan dan Pembelajaran Kimia, 2026)
Abstract: The Effect of Cooperative Learning on Improving High School Students' Chemistry Learning Outcomes in Indonesia. Objectives: This study aims to analyze the application of the Cooperative Learning model in chemistry learning in Indonesian high schools and its effectiveness on student learning outcomes. Methods: The study was conducted using the Systematic Literature Review (SLR) method based on the PRISMA guidelines with data sources from Google Scholar, SINTA, Garuda, and Scopus for the period 2015–2025. Of the 126 articles found, 20 articles met the inclusion criteria for further analysis. Findings: The results showed that cooperative learning consistently had a positive impact on students' cognitive learning outcomes, motivation, activity, and science process skills. The STAD model was the most dominant type used and provided the highest learning outcome improvement (30–35%), followed by Jigsaw (25–30%), TAI, Cooperative Script, GI, and CRH. Conversely, the Rotating Trio Exchange model showed low and inconsistent effectiveness. The publication trend graph shows a significant increase in research in the 2017–2025 period. The successful implementation of Cooperative Learning is influenced by the teacher's ability to manage groups, the availability of learning media, and the readiness and heterogeneity of students. Conclusion: Thus, Cooperative Learning, especially the STAD and Jigsaw models, has been proven to be relevant and effective in improving the quality of chemistry learning in high schools.